2016
DOI: 10.1002/jgm.2891
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of intra‐articular injection of ribbon‐type decoy oligonucleotides for hypoxia inducible factor‐1 on joint contracture in an immobilized knee animal model

Abstract: The present study demonstrates the important role of HIF-1 in the initial progression of immobilization-induced joint contracture, and indicates the possibility of molecular treatment to prevent the progression of joint contracture prior to intervention with physical therapy. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…Previous studies have shown an immobilization‐related increase in connective tissue, which is consistent with our results. The reduction of ROM in the immobilized knee joint accompanied by synovial hypertrophy in the mouse model has been demonstrated . Moreover, previous studies found that the extensibility of the joint capsule depends on its thickness .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous studies have shown an immobilization‐related increase in connective tissue, which is consistent with our results. The reduction of ROM in the immobilized knee joint accompanied by synovial hypertrophy in the mouse model has been demonstrated . Moreover, previous studies found that the extensibility of the joint capsule depends on its thickness .…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies suggested that immobilization induces joint capsule fibrosis . Higher amounts of type I collagen have been reported in the capsules of immobilized knees, and synovial hypertrophy with fibrosis in the joint capsule has been observed after immobilization . These studies suggest that joint capsule fibrosis may be a primary cause of pathology in joint contractures.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…In the existing studies on medical inhibition of the development of joint contracture (Table 2), an improvement of the range of motion could be achieved mostly after intraarticular application of the respective active agents. 16,17,64,[95][96][97][98][99][100][101][102][103][104] Although these results constitute an opportunity for the development of a medical treatment of patients with PTJS, the intraarticular application is unfavorable for a number of reasons: i) it is a painful and invasive procedure for the patient, ii) it bears the risk of septic arthritis, iii) it might damage the articular cartilage by chondrotoxic effects or iv) weaken the capsule and ligaments of the knee. [105][106][107] Based on the rabbit models of PTJS of Hildebrand et al and Nesterenko et al, our group established a rat model of PTJS of the knee joint that included a rupture of the posterior joint capsule, a hemarthrosis, an intraarticular bone damage and a temporary fixation of the joint.…”
Section: Atorvastatin Inferior Capsulementioning
confidence: 99%
“…In a ribbon-type (dumbbell-type) decoy ODN, both double-stranded termini of the decoy ODN are linked by a circular structure of nucleic acids, because degradation of decoy ODN by nuclease begins at the site where ODN ends. 52,85,86) Indeed, our previous study reported that ribbon-type decoy ODN against NFκB and ets could inhibit AAA progression in an elastase-induced rat AAA model despite systemic administration. 87) In addition, our recent study and other studies have demonstrated that sense and antisense strands of decoy ODN were linked with a chemical spacer instead of nucleic acids.…”
Section: Structural Modification Of Decoy Odn and Delivery Systemmentioning
confidence: 99%